EVALUATION OF SKELETAL MUSCLE RELAXANT ACTIVITY OF CYMBOPOGON CITRATUS IN MICE - MISHRA, APOORAV; SINGH, AJEET PAL; SINGH, AMAR PAL (International Journal of Current Pharmaceutical Research, 2025)
Objective: To evaluate skeletal muscle relaxant of Ethanolic extracts of Cymbopogon citratus leaves in albino mice by using Rota rod method and Inclined plane model. Methods: Healthy, adult Swiss albino mice of either sex weighing (25-40 g), maintained under standard laboratory conditions, at temperature 25±2 °C and a 12 h light-12 h dark period employed for the experimentation. Food and water provided ad libitum. Results: In the present study, the skeletal muscle relaxant activity of ethanolic extract of Cymbopogon citratus in Swiss albino mice at the dose of 250 and 500 mg/kg with oral administration respectively. Conclusion: In conclusion, both the doses of 250 and 500 mg/kg with oral administration have shown significant results as skeletal muscle relaxant effect using rota rod method and Inclined plane model.